Carotid Artery Wall Motion Estimation from Consecutive Ultrasonic Images: Comparison between Block-Matching and Maximum-Gradient Algorithms - Effat Soleimani (Journal of Tehran University Heart Center, 2011)
Background: Radial movement of the arterial wall is a well-known indicator of the mechanical properties of arteries in arterial disease examinations. In the present study, two different motion estimation methods, based on the block-matching and maximum-gradient algorithms, were examined to extract the radial displacement of the carotid artery wall.